Environmental justice and climate change policies - Resnik, David B. (Bioethics, 2022)
Climate change is an environmental justice issue because it is likely to cause disproportionate harm to low‐income countries and low‐income populations in higher‐income countries. While climate change mitigation and adaptation policies may be able to minimize these harms, they could make them worse unless they are developed and implemented with an eye toward promoting justice and fairness. Those who view climate change as an environmental justice issue should be wary of endorsing policies that sound like they promote the cause of social and economic justice, but in fact do not. While climate change policies may help to mitigate the effects of climate change on poor people, there is no guarantee that they will be just at the local, national, or global level. Those who care about global climate justice must remain actively engaged in policy formation and implementation to ensure that justice does not get shortchanged in the response to global warming.